2005
DOI: 10.2298/aci0502081b
|View full text |Cite
|
Sign up to set email alerts
|

Rigid-fix Pins fixation and LCA reconstruction with semitendinosus/gracilis autograft

Abstract: ACL reconstruction techniques highly developed during the decades and biomechanical tests for hamstrings graft showed much in advance loading and stiffness comparing BPTB grafting. We have made joint analysis of 30 patients with semitendinosus / gracilis ACL reconstruction. Choice for proximal fixation was Mitek Rigid-fix Pins technique and bioactive screws for distal fixation; in 18 cases bioactive screws were used for femoral and tibial graft fixation. Lysholm score and knee clinical tests were parameters us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…[21][22][23] Numerous studies have evaluated the clinical outcome of rigid fix technique in ACL reconstruction and some studies have compared this method of fixation with others to have a definite conclusion. 10,12 While comparing the Rigid-fix (n = 71) and PINN ACL cross pin techniques (n = 56) in 127 patients (N), Seo et al 10 did not observe any statistical difference in IKDC score and Lysholm score; however, 5 cases (7%) in rigid fix group and 40 cases (71%) in PINN ACL cross pin group were found to be associated with perioperative complications with statistical difference (p < 0.0001). They concluded that there was no resultant difference between the employment of PINN-ACL Cross Pin and Rigid-fix as femoral graft fixation for ACL reconstruction with hamstring tendon.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…[21][22][23] Numerous studies have evaluated the clinical outcome of rigid fix technique in ACL reconstruction and some studies have compared this method of fixation with others to have a definite conclusion. 10,12 While comparing the Rigid-fix (n = 71) and PINN ACL cross pin techniques (n = 56) in 127 patients (N), Seo et al 10 did not observe any statistical difference in IKDC score and Lysholm score; however, 5 cases (7%) in rigid fix group and 40 cases (71%) in PINN ACL cross pin group were found to be associated with perioperative complications with statistical difference (p < 0.0001). They concluded that there was no resultant difference between the employment of PINN-ACL Cross Pin and Rigid-fix as femoral graft fixation for ACL reconstruction with hamstring tendon.…”
Section: Discussionmentioning
confidence: 98%
“…2 Expansion fixation that is based on pressfit fixation of a graft into the femoral tunnel by employing more than one cross pin has been reported to render satisfying results in biomechanical and clinical studies. 10,12,14,19 This fixation provides secure fixation to the graft as the cross pins applied transversely through the graft, imparts a centrifugal pressure on the femoral tunnel. Nevertheless, the treatment results depend on the press-fit of the graft, bone density around the femoral tunnel, and correct placement of the cross pins through the graft tendon.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations